2017
DOI: 10.3390/su9060944
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Trade Relations and the Spatial-Temporal Evolution of Geo-Economy between China and Vietnam

Abstract: Abstract:With the increasing economic importance of the Asia-Pacific Region, the economic interdependence among countries in the region has gradually enhanced. With the continuous opening up of the two countries, Sino-Vietnamese economic relations have also been deepened. However, the export trade between Vietnam and China has been competitive. China and Vietnam seek to dominate or join an agreement that is conducive to their own trade, which also exacerbates the trade competition between the two countries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The BRI nations Poland, Austria, and the Czech Republic collectively account for 17.9% of the region's untapped potential, offering a direct route into the EU (Cameron, Cuyvers, Fu, & Viviers, 2021). Ma, Liu, and Ge (2017) East Asia (ERIA) in 2020 (Pan et al, 2021).…”
Section: Manufacturing Relocations Were Pushed By Cost Hikes and Indu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The BRI nations Poland, Austria, and the Czech Republic collectively account for 17.9% of the region's untapped potential, offering a direct route into the EU (Cameron, Cuyvers, Fu, & Viviers, 2021). Ma, Liu, and Ge (2017) East Asia (ERIA) in 2020 (Pan et al, 2021).…”
Section: Manufacturing Relocations Were Pushed By Cost Hikes and Indu...mentioning
confidence: 99%
“…Ma, Liu, and Ge (2017) assessed the competitiveness of China and Vietnam based on Relative Trade Advantages (RTAs) covering trade data from 2005 to 2014 and found that Vietnam was more competitive in apparel, clothing, and footwear than China. The U.S.‐China trade war opened up market opportunities for other countries, especially Vietnam, because of its low labor costs and flexible production capacity (Itakura, 2020; Tien & Anh, 2019; Tien, Vu, Dung, Doan, & Duc, 2019; Wang, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the increasing economic importance, customers are becoming increasingly demanding (Ma et al, 2017). These demands put pressure on businesses to establish innovations in their work, for example by outsourcing the maintenance operations for building equipment (David et al, 2017;Gilson et al, 2016).…”
Section: Rezultati I Raspravamentioning
confidence: 99%
“…); countries of Middle East specialized in the export of raw materials and fossil fuels little to none overlap with Chinese exports (Saudi Arabia, Iran, Qatar, Kuwait). The growing competition between China and Vietnam in textiles, apparel and clothing, and footwear was outlined in 2017 in an extensive study of comparative trade relations of these countries (Ma et al, 2017). Outlined developments in trade are also accompanied by similar changes in finances and politics with Vietnam becoming the new destination of USA foreign investment infusions while the modernization of the country and rapid development of IT and hi-tech industries are continually pushing the competition with China even further (Pritesh, 2020).…”
Section: Results and Analysismentioning
confidence: 99%